A Five-year Report on Body Packing and Body Stuffing in Isfahan - Farzad Ghesglaghi; Mojgan Gomari; Shaun L. Greene; Joe Anthony Rotella; Shayan Gheshlaghi (Iranian Journal of Toxicology, 2021)
Background: Body packing and body stuffing of illicit drugs have increased in recent decades. The drug contents of the packages vary from region to region, and there are controversies surrounding the diagnostic and therapeutic methods. The aim of this study was to explore the clinical presentations, diagnostic and therapeutic measures, and the subsequent clinical outcomes of drug concealment by people. Methods: A retrospective analysis was performed on data for all cases of body packing and body stuffing that were referred to a university hospital, in Isfahan, Iran, from Mar. 2013 to Feb. 2018. Results: Sixty-eight body stuffers and 18 body packers (n=86) were included in this study. Seventy-eight patients (90.7%) were male, mostly aged between 20 to 40 years. There was no significant difference between the two groups with respect to the signs and symptom, hospital stay, treatment and clinical outcomes. Heroin and crystal methamphetamine, n=52 (60%) and n=22 (25%), respectively, were the most substances detected, irrespective of the concealment method. Abdominal X-ray and CT scan tests were positive for the detection of at least one packet in each of the 94.4% of the patients. Conclusion: Heroin and crystal methamphetamine were the most common substances concealed in the bodies of the patients. Based on our findings, CT scan was more sensitive than abdominal X-ray test in the detection of illicit drug packets concealed in the patients. Close observation and whole bowel irrigation were effective therapeutic modalities in most cases. All cases were fully recovered and discharged from the hospital.